Study guides

Q: 12x-8 equals 10x plus 4

Write your answer...

Submit

Related questions

y=-10x-4

5x + 4 = 10x - 5 10x - 5x = 4 + 5 5x = 9 x = 1.8

x = 4

10x + 13 = 17 ie 10x = 17 - 13 so x = 4/10 = 0.4

2x + (10x - 4) = 20 2x + 10x - 4 = 20 12x - 4 = 20 12x = 24 x = 2

If: 4y+10x = 16Then: 4y = -10x+16And: y = -2.5x+4

-4 = 17x so x = -4/17

7x = 3 x = 3/7

6-3x = 5x-10x+2 4 = 8x-10x 4 = -2x x = -2

There is no symbol between 7x and 31. Please resubmit using words eg "plus", "equals" etc.

10x + 13 = 1710x = 17-1310x = 4x = 4/10x = 0.4

10x + 2y + 8z - 5x + 4z - 4y = 10x - 5x + 2y - 4y + 8z + 4z = (10 - 5)x + (2 - 4)y + (8 + 4)z = 5x - 2y + 12z

x2+10x+1 = -12+2x x2+8x+13 = 0 The solution: x = -4 + the square root of 3 or x = -4 - the square root of 3

They intersect at the point of: (-3/2, 11/4)

6x+58=10x+14 first move the 58 to the other side by subtracting it. 6x=10x-48 Then you move the 10x to the other side by subtracting it. -4x=-48 Then you divide both sides by -4 x=12 is you answer.

12x - 6 = 10x +2 12x - 10x = 2 + 6 2x = 8 x = 4

Complete the squares: x2 - 10x + 25 + y2 + 4y + 4 - 52 = 25 + 4 = 29 x2 - 10x + 25 + y2 + 4y + 4 = 52 + 29 = 81 So the radius is sqrt(81) = 9

Calculate 10^2 - 4*(-16)*(-20)

Do a bit of rearrangement: 1: 10x + 2 = 8y; 2: 8y = 59 - 9x so 10x + 2 = 59 - 9x so 19x - 57 making x = 3 and y is therefore 4.

3x-13x+4=0 -10x+4=0 4=10x 4/10=x simplified: x= 2/5

x = - 4 - or + the square root of 3 Solved by using the quadratic equation formula.

Given: x2 + y2 - 10x + 4y + 4 = 0 First, we'll move our constants to the right: x2 + y2 - 10x + 4y = -4 Then group terms with the same variables together: x2 - 10x + y2 + 4y = -4 Then complete the squares: x2 - 10x + 25 + y2 + 4y + 4 = -4 + 25 + 4 (x - 5)2 + (y + 2)2 = 25 And there we have it. This is an equation for a circle whose center point is at (5, -2), with a radius of √25, which equals 5.

If 10x + 6y = 24, y = (24 - 10x)/6 = 4 - (5/3)x. The slope of a line with an equation written in this format is the coefficient of x, therefore -(5/3).

x2+10x+1 = -12+2x x2+10x-2x+1+12 = 0 x2+8x+13 = 0 Solving by using the quadratic equation formula: x = - 4 - or + the square root of 3

x2+10x+24 = (x+6)(x+4) when factored